MANAJEMEN PROYEK DI NEGARA-NEGARA BERKEMBANG (SUATU TINJAUAN PUSTAKA) - Candra Dharmayanti, G.A.P. (Jurnal Ilmiah Teknik Sipil; Vol. 12, No. 1 Januari 2008)
In order to manage international projects successfully, there are many aspects that should be considered by a project manager. One of it, is by overcoming obstacles dealing with the characteristics of the countries where the projects are executed. A project manager must be able to read the opportunities that can be achieved and understand how to cope the obstacles dealing with the conditions where the project is carried out. Although each country usually has unique characteristics, there are several main aspects dealing with it that should be put in mind when managing international projects. In this literature study, it will be discussed main issues dealing with managing projects that particularly carried out in developing countries.
Keywords: manajemen proyek, negara berkembang